2011
DOI: 10.1007/s11356-011-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcium invigorates the cadmium-stressed Brassica napus L. plants by strengthening their photosynthetic system

Abstract: This study suggests that Ca(2+) in the proximity of plasma membrane is proficient in alleviating Cd toxicity by reducing the cell-surface negativity and competing for Cd(2+) ion influx. Consequently, both the plant growth and activity of diurnal photosynthetic system remain the least altered under Cd-provoked toxicity stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 38 publications
6
32
0
1
Order By: Relevance
“…The authors further observed that higher Cd levels were responsible for damaging chloroplasts and mitochondria. Reduction in plant growth under Cd stress was also suggested by Wan et al (2011), who observed significant reductions in photosynthesis and nutrient uptake in Brassica napus seedlings.…”
Section: Cadmium (Cd)supporting
confidence: 60%
“…The authors further observed that higher Cd levels were responsible for damaging chloroplasts and mitochondria. Reduction in plant growth under Cd stress was also suggested by Wan et al (2011), who observed significant reductions in photosynthesis and nutrient uptake in Brassica napus seedlings.…”
Section: Cadmium (Cd)supporting
confidence: 60%
“…1 and 2). There have been reports showing that exogenous Ca application alleviates Cd stress in plants (Ismai, 2008;Wan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2; 3A). Decrease in chlorophyll contents might be result of displacement of Mg required for chlorophyll biosynthesis as suggested by Wan et al (2011) and/or ultra-structural alteration of chloroplast under metal toxicity (Yruela, 2009;Gill et al, 2015). Damage to photosynthetic machinery seems to be associated with Cu translocation into leaf tissues, which could impair lamalar membrane of choloroplast (Najeeb et al, 2009).…”
Section: Effect Of Copper On Plant Morphology and Compositionmentioning
confidence: 99%